Biliary Atresia Treatment: Can Shear Wave Elastography Predict Kasai Procedure Outcomes? - Sekarsari Damayanti, Gema Ramadhan Muhammad, Rinaldhy Kshetra, Prihartono Joedo (Advanced Ultrasound in Diagnosis and Therapy)
Objective Biliary atresia is a significant cause of neonatal pathological jaundice, demanding effective interventions such as the Kasai procedure to impede its advancement. Previous research highlights the potential of shear wave elastography for assessing liver fibrosis and the subsequent necessity for liver transplantation following Kasai procedure. This underlines the significance of our study in investigating shear wave elastography as a predictive tool for the success of Kasai procedure in biliary atresia patients. Methods This retrospective case-control comparative study analyzed data from biliary atresia patients who underwent shear wave elastography ultrasound and the Kasai procedure at our center from 2020 to 2022. Successful Kasai outcomes formed the case group; unsuccessful, the control. We calculated the mean shear wave elastography values for each group and established a predictive Kasai success cut-off using SPSS for statistical analysis. Results Twenty-one subjects, with 8 males and 13 females (median age: 82 days), were evaluated. Of the 21 subjects, 9 (42.9%) had successful Kasai outcomes, while 12 (57.1%) were unsuccessful. There are statistically different values between two groups, such as the shear wave elastography value (P = 0.001). The optimal cut-off point of shear wave elastography value to predict the success of Kasai procedure is 2.21 m/s or 14.4 kPa (sensitivity 88.9%, specificity 83.3%, accuracy 85.7%, PPV 87.65%, NPV 84.91%), with an AUC of 0.889 (95%CI = 0.75-1.00), OR = 10.50 (1.360-81.053). Conclusion This study demonstrates shear wave elastography’s potential utility in predicting Kasai procedure success for biliary atresia patients, suggesting its role as a valuable prognostic tool.